Migratory delay leads to reduced passage success of Atlantic salmon smolts at a hydroelectric dam. Issue 4 (10th October 2016) - Nyqvist, Daniel; Greenberg, Larry A.; Goerig, Elsa; Calles, Olle; Bergman, Eva; Ardren, William R.; Castro‐Santos, Theodore
Abstract: Passage of fish through hydropower dams is associated with mortality, delay, increased energy expenditure and migratory failure for migrating fish and the need for remedial measures for both upstream and downstream migration is widely recognised. A functional fish passage must ensure safe and timely passage routes that a substantial portion of migrating fish will use. Passage solutions must address not only the number or percentage of fish that successfully pass a barrier, but also the time it takes to pass. Here, we used radiotelemetry to study the functionality of a fish bypass for downstream‐migrating wild‐caught and hatchery‐released Atlantic salmon smolts. We used time‐to‐event analysis to model the influence of fish characteristics and environmental variables on the rates of a series of events associated with dam passage. Among the modelled events were approach rate to the bypass entry zone, retention rates in both the forebay and the entry zone and passage rates. Despite repeated attempts, only 65% of the tagged fish present in the forebay passed the dam. Fish passed via the bypass (33%), via spill (18%) and via turbines (15%). Discharge was positively related to approach, passage and retention rates. We did not detect any differences between wild and hatchery fish. Even though individual fish visited the forebay and the entry zone on multiple occasions, most fish passed during the first exposures to these zones. This study underscores the importance of timeliness to passage success and the usefulness of time‐to‐event analysis for understanding factors governing passage performance.